Fractional-order control of cooperative robots - Figueiredo, C. M. (2019)
In this paper it is studied the implementation of fractional-order algorithms in the position/force control of two cooperating robotic manipulators. The system performance is analyzed in the time and frequency domains. We analyze and compare different control methodologies such as the integer and the fractional-order PID presenting the simulation results assessing the performance of the proposed fractional-order algorithms.